2020
DOI: 10.3390/wevj11010022
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Case for Electric Vehicles in Public Sector Fleets: An Italian Case Study

Abstract: The paper investigates whether it makes economic sense to use electric vehicles (EVs) in the public sector fleet. Thanks to the data collected in 2018 in 77 public sector entities in an Italian region, Friuli Venezia Giulia, we compare the total cost of ownership of a battery electric vehicle with that of a similar internal combustion engine one. We provide estimates for four scenarios (status quo, social cost internalization, price discounts and a combination of the last two) for three groups of public entiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Numerous works discuss the investment in EVs for public transportation from various perspective. The most common economic indicators include total cost of ownership (TCO), least cost, net present value (NPV), payback period (PBP), internal rate of return (IRR), and return on investment (ROI) [11][12][13][14]. For instance, [12] compared the TCO of battery EVs and internal combustion vehicles for local health authorities, municipalities, and special purpose authorities between passenger cars and mixed-use small light commercial vehicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works discuss the investment in EVs for public transportation from various perspective. The most common economic indicators include total cost of ownership (TCO), least cost, net present value (NPV), payback period (PBP), internal rate of return (IRR), and return on investment (ROI) [11][12][13][14]. For instance, [12] compared the TCO of battery EVs and internal combustion vehicles for local health authorities, municipalities, and special purpose authorities between passenger cars and mixed-use small light commercial vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The most common economic indicators include total cost of ownership (TCO), least cost, net present value (NPV), payback period (PBP), internal rate of return (IRR), and return on investment (ROI) [11][12][13][14]. For instance, [12] compared the TCO of battery EVs and internal combustion vehicles for local health authorities, municipalities, and special purpose authorities between passenger cars and mixed-use small light commercial vehicles. The research highlights economic sense to adopt EVs for a positive although relatively small percentage of the public sector fleet under the current price and cost structure.…”
Section: Introductionmentioning
confidence: 99%
“…Dumortier et al [48] pointed out that consumers assess the current expenditure more than the long-term savings of EVs. Danielis et al [49] found that even though the energy preservation of EV can save substantial money, only consumers with long driving ranges can extensively profit from it. Though the benefits of EVs regarding price may appeal to some consumers, these advantages are not evident in the short term.…”
Section: Purchasing Ev Pricementioning
confidence: 99%
“…For a vehicle, this includes one-time costs like the purchase costs, but also recurring expenses like fuel and maintenance cost [14]. TCO models might have two cost components: one including the costs borne by the vehicle user (the consumer-oriented TCO), and one including the costs borne by society, as for example air and noise pollution (the society-oriented TCO) [15]. The TCO can be separated into capital costs (the cost of purchasing vehicles) and operational costs (the cost of using vehicles).…”
Section: Introductionmentioning
confidence: 99%